Structural and Optical Properties of ZnWO4:Er3+ Crystals. (25th August 2013) - Minh, Nguyen Van; Hung, Nguyen Manh; Xuan Thao, Du Thi; Roeffaers, Maarten; Hofkens, Johan
Abstract : Erbium ion- (Er 3+ -) doped ZnWO4 crystals were synthesized via a hydrothermal method with different erbium concentrations. The prepared materials were characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM), and Raman, UV-Vis, and photoluminescence (PL) spectroscopy. For ZnWO4 :Er 3+ crystals, a pure phase of ZnWO4 was obtained without any evidence of impurity present. The SEM images show that the grain size and morphology of ZnWO4 :Er 3+ material depends on the Er 3+ -dopant concentration. The UV-Vis spectra of ZnWO4 :Er 3+ compounds exhibited an absorption band at about 323 nm (3.83 eV) stemming from the [WO4 ] 2− . Other absorption bands centered at 367, 379, 408, 490, and 522 nm are related to Er 3+ -ion transitions. Room temperature PL spectra of the ZnWO4 :Er 3+ compounds exhibited visible emission at 515–540 and 545–565 nm corresponding to the 2 H11/2 − 4 I15/2 and 4 S3/2 − 4 I15/2 transitions of Er 3+ ions, respectively.